2011
DOI: 10.1111/j.1742-7843.2011.00812.x
|View full text |Cite
|
Sign up to set email alerts
|

Echinomycin Decreases Induction of Vascular Endothelial Growth Factor and Hepatocyte Regeneration in Acetaminophen Toxicity in Mice

Abstract: Up-regulation of vascular endothelial growth factor (VEGF) is important to hepatocyte regeneration in the late stages of acetaminophen (APAP) toxicity in the mouse. The following study was conducted to examine the relationship of hypoxia inducible factor 1α (HIF-1α) to VEGF and hepatocyte regeneration in APAP toxicity by using an inhibitor of HIF-1α DNA-binding activity, echinomycin (EC). B6C3F1 male mice were treated with APAP (200 mg/kg IP), followed by EC (0.15 mg IP) and killed at 4 hr. Serum ALT, necrosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 47 publications
0
3
1
Order By: Relevance
“…In this study, the number of PCNA positive cells was large, and the vast majority of PCNA positive cells were inflammatory cells, this is different from the other studies which have shown hepatocytes at bordering area of necrosis express PCNA during injury progression [ 37 , 38 ]. There are two possibilities for this phenomenon: (1) The specificity and the sensitivity of the first antibody to PCNA might markedly influence the results, because the other two studies used monoclonal antibody to PCNA from DakoCytomation (Carpinteria, CA, USA) and Abcam, (Cambridge, MA), our PCNA staining kit was purchased from Invitrogen (Camarillo, CA, USA).…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…In this study, the number of PCNA positive cells was large, and the vast majority of PCNA positive cells were inflammatory cells, this is different from the other studies which have shown hepatocytes at bordering area of necrosis express PCNA during injury progression [ 37 , 38 ]. There are two possibilities for this phenomenon: (1) The specificity and the sensitivity of the first antibody to PCNA might markedly influence the results, because the other two studies used monoclonal antibody to PCNA from DakoCytomation (Carpinteria, CA, USA) and Abcam, (Cambridge, MA), our PCNA staining kit was purchased from Invitrogen (Camarillo, CA, USA).…”
Section: Discussioncontrasting
confidence: 95%
“…There are two possibilities for this phenomenon: (1) The specificity and the sensitivity of the first antibody to PCNA might markedly influence the results, because the other two studies used monoclonal antibody to PCNA from DakoCytomation (Carpinteria, CA, USA) and Abcam, (Cambridge, MA), our PCNA staining kit was purchased from Invitrogen (Camarillo, CA, USA). (2) Animal species might also influence the results, because 24 hrs after APAP administration, PCNA expression was apparent in B6C3F1 mice [ 37 ] and B6J129 SVF2 mice [ 38 ], however, PCNA staining was negative or occasional in C57/BL6 mice in our study at 24 h time point, and our result was consistent with another study [ 32 ] in which BrdU (5-bromo-2-deoxyuridine) immunohistochemistry was performed to detect hepatocyte regeneration in C57/BL6 mice.…”
Section: Discussionmentioning
confidence: 99%
“…Echinomycin, a small molecule inhibitor of HIF-1 DNA binding, lowered VEGF protein expression in APAP toxicity in mice (Micheli-Halle, 2011). Despite lower HIF-1α induction, APAP/TFP mice had relatively higher levels of hepatic VEGF at 8 and 24 h, compared to the APAP mice (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…animal species also markedly influence the results: 24 hrs after APAP administration, PCNA expression is apparent in B6C3F1 mice [42] and B6J129 SVF2 mice [43], however, BrdU and PCNA (Invitrogen) methods only show negative or occasional positive staining in C57/BL6 mice [10,11,44]; more importantly, 48 hrs after APAP subjected to C57/BL6 mice, both PCNA (Invitrogen) and BrdU methods show that the extent of hepatic PCNA / BrdU expression depends mainly on the extent of liver damage, because the expression of hepatic PCNA /BrdU is significantly correlated with the area of hepatocyte necrosis for each mouse: larger size of necrosis has larger number of PCNA/BrdU positive cells, while improved liver repair with smaller necrotic size has smaller number of PCNA/BrdU positive cells, this is not conventionally expected [10,11,44]. In addition, the number of PCNA-positive non-parenchymal cells is 10 times larger than the number of BrdU-positive hepatocyte in C57/BL6 mice during APAP hepatotoxicity [11], suggesting that currently the nonparenchymal cells are likely underestimated, and the number of the non-parenchymal cell loss could be larger than the hepatocyte loss during APAP toxicity, the latter could explain the impaired immune function and the higher incidence of gram-negative infection during hepatotoxicity [11,45], further investigation is needed to focus on non parenchymal cell loss in APAP overdose.…”
Section: The Role Of Nf-kb In Apap Overdosementioning
confidence: 99%